Evaluation of the Effect of Continuous and Interval Aerobic Training on Survivin Gene Expression and Cytochrome C in Myocardial Tissue of Rats Modeled with Myocardial Infarction - Mardani, Bahareh; Keshavarz, Saeed; Mojtahedi, Hossein; Sarrami, Leila (Health Nexus, 2026)
This study aimed to investigate the effects of moderate-intensity continuous training (MICT) and high-intensity interval training (MIHIIT) on Survivin gene expression and Cytochrome C levels in myocardial tissue of rats modeled with myocardial infarction. In this experimental study, 30 adult male Wistar rats (10–12 weeks, 275 ± 25 g) were assigned to five groups: healthy control, sham, myocardial infarction (MI), MICT, and MIHIIT. The MI model was induced through left anterior descending coronary artery occlusion and confirmed by echocardiography. Training protocols were performed for 8 weeks, five sessions per week. The MICT group performed continuous running at moderate intensity (15–23 m/min, 50 minutes), while the MIHIIT group completed interval running consisting of 7 sets of high-intensity bouts (20–28 m/min, 4 minutes) with active recovery periods (11–17 m/min, 3 minutes). Survivin gene expression was measured using RT-qPCR, and Cytochrome C levels were quantified using ELISA. Data were analyzed using MANOVA, ANOVA, and Tukey post-hoc tests. Myocardial infarction caused a significant increase in Cytochrome C levels and a reduction in Survivin expression compared to the healthy and sham groups (p < .001). Both types of aerobic training significantly reversed the infarction-induced alterations; Cytochrome C levels were reduced, and Survivin expression returned to levels comparable to the control group. When comparing the two protocols, interval training (MIHIIT) produced a greater increase in Survivin expression (p ≈ .046), while both exercise types demonstrated similar effects on reducing Cytochrome C. Both continuous and interval aerobic training restore the survival/death balance in myocardial tissue following infarction by reducing oxidative stress and enhancing Survivin expression. These findings reinforce the role of aerobic exercise as an effective non-pharmacological intervention in cardiac rehabilitation.